UTILIZATION OF PHYSIOTHERAPY SERVICES IN THE WORD - SIMON-UGRON, Ágnes (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2017)
Introduction. Both at the national and international levels, direct access for patients to physical therapy services is currently under debate. Direct access for patients seeking physical therapy care might reduce waiting time and costs, and thus be of benefit for patients and health insurance companies. Objectives. The purpose of this study was to assess current evidence and evaluate the impact of physical therapy guideline adherence on subsequent healthcare costs and utilization for patients. Materials and methods. Data Sources is from Value in Health (2011-2016) and an electronic search was conducted in PubMed, at the 15th of January 2017. Key words were used independently and in combination including: physical therapy, physiotherapy and utilization. Results. The initial search of each database results were as follows: Value in Health (15) and Medline (PubMed) (41). Thus, a total of 56 results were identified. After applying the inclusion criteria and omitting duplicates, 22 articles remained and were included in this review. Conclusion. Utilization of physiotherapy in the word is different but where they oft use this therapy the health care costs became reduced. REZUMAT. Utilizarea serviciului de kinetoterapie/fizioterapie în lume. Introducere. Atât la nivel național cât și internațional, un acces direct la serviciile de fizioterapie/kinetoterapie pentru pacienți este în dezbatere în prezent. Accesul direct pentru pacienții care doresc fizioterapie/kinetoterapie poate reduce costurile și timpul de așteptare, și, prin urmare, o să fie benefică pentru pacienți și pentru societățile de asigurări de sănătate. Obiective: Scopul acestui studiu a fost de a evidenția și evalua prin dovezi curente impactul fizioterapiei/ kinetoterapiei cu orientare privind costurile asistenței medicale și utilizarea către pacienți. Material și metode. Bazele de date utilizate: Value in Health (2011-2016) și pentru căutare electronică: PubMed, în data de 15 ianuarie 2017. Cuvintele de cheie au fost utilizate în mod independent și în combinație incluzând: fizioterapie, kinetoterapie și utilizare. Rezultate. Căutarea inițială în baza de date a fiecărui rezultat au fost următoarele: Value in Health (15) și Medline (PubMed) (41). Astfel, un total de 56 rezultate au fost identificate. După aplicarea criteriilor de includere și omiterea duplicatelor, 23 de articolele au fost incluse și rămâneau în această recenzie. Concluzii: Utilizarea kinetoterapiei/fizioterapiei în lume este diferit, dar unde se aplică frecvent această terapie și costurile asistenței medicale devin mai reduse. Cuvinte cheie: fizioterapie, kinetoterapie, utilizare.